2014
DOI: 10.3390/su6020589
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Built Environment in Reducing Vehicle Miles Traveled Accounting for Spatial Heterogeneity

Abstract: Abstract:In recent years, increasing concerns over climate change and transportation energy consumption have sparked research into the influences of urban form and land use patterns on motorized travel, notably vehicle miles traveled (VMT). However, empirical studies provide mixed evidence of the influence of the built environment on travel. In particular, the role of density after controlling for the confounding factors (e.g., land use mix, average block size, and distance from CBD) still remains unclear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Therefore, car ownership and use control policy needs to be developed based on local conditions. However, there are some similar results with prior studies conducted in western countries [16,[22][23][24]40]. It was found that residential density, land use mixture, bus stop density, and intersection density had significant effects on household car ownership.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, car ownership and use control policy needs to be developed based on local conditions. However, there are some similar results with prior studies conducted in western countries [16,[22][23][24]40]. It was found that residential density, land use mixture, bus stop density, and intersection density had significant effects on household car ownership.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Ding et al built a multilevel model to explore the relationship between the built environment and work-related VMT and claimed that the increasing distance from CBD generated more VMT. After the spatial heterogeneity is taken into consideration, the model performs better than the simple models [24]. However, the spatial relationship between groups cannot be captured with a multilevel model, which is also viewed as a way to display the effect of location [28].…”
Section: Spatial Effects In City Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth enriches residents and may then increase their vehicular demands. In addition, residents' increased income may result in changes to the built environment of their homes and workplaces (Ding et al, 2014) and to their attitudes toward the environment (Grossman and Krueger, 1991) 2 , transportation systems and infrastructure (Sadorsky, 2014) and green innovation (Qi et al, 2010). All these changes are relevant to vehicular CO2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Their uses are numerous and widely diverse. They cover areas of urban and regional planning [1]- [6], environmental monitoring and assessment [7]- [10], change detection [11]- [17], simulation and prediction of future spatial and man-made phenomena [18]- [21], and others. They are time sensitive as well as content important.…”
Section: Introductionmentioning
confidence: 99%